A novel nanostructured supramolecular hydrogel self-assembled from tetraphenylethylene-capped dipeptides. Issue 30 (6th July 2016) - Yeh, Mei-Yu; Huang, Chen-Wei; Chang, Jui-Wen; Huang, Yu-Tang; Lin, Jhong-Hua; Hsu, Shu-Min; Hung, Shih-Chieh; Lin, Hsin-Chieh
Abstract : We study the structure–assembly relationship of TPE-capped dipeptides; one of them shows the largest lateral ratio of TPE-capped nanobelts reported to date. Abstract : Herein, we report a tetraphenylethylene-diglycine (TPE-GG) hydrogelator from a systematic study of TPE-capped dipeptides with various amphiphilic properties. From a chemical design, we found that the hydrogelation of TPE-GG molecules can be utilized to generate supramolecular nanostructures with a large TPE-based nanobelt width (∼300 nm) and lateral dimension ratio (>30 fold). In addition, TPE-GG has the lowest molecular weight and minimum number of atoms compared to any TPE-capped peptide hydrogelator reported to date. This minimal self-assembled hydrogelator can fundamentally achieve the gel features compared with other TPE-capped peptides. A combined experimental and computational study indicates the π–π interactions, electrostatic interactions and hydrogen-bonding interactions are the major driving forces behind the formation of self-assembled nanobelts. This study demonstrates the importance of structure–property relationships and provides new insights into the design of supramolecular nanomaterials.